A Preliminary Note on Variation in Catechin Content of Acacia catechu Tree with its Age in the Siwalik Forest Division of the Uttar Pradesh Forests - Sharma, O. P.; Dobhal, N. P. (Indian Forester, 1969)
Percentages of heartwood, total water solubles and catechin content of Acacia calechu trees of different age class cultivated in four different localities of Siwalik Forest Division of Dehra Dun are described. Observations on the occurrence of kheersal (natural deposit of condensed catechin) are also recorded.